The diverse roles of macrophages in metabolic inflammation and its resolution - Guha Ray, Aleepta; Odum, Oluwatomilayo Patience; Wiseman, Destini; Weinstock, Ada (Frontiers in Cell and Developmental Biology, 2023)
Macrophages are one of the most functionally diverse immune cells, indispensable to maintain tissue integrity and metabolic health. Macrophages perform a myriad of functions ranging from promoting inflammation, through inflammation resolution to restoring and maintaining tissue homeostasis. Metabolic diseases encompass a growing list of diseases which develop from a mix of genetics and environmental cues leading to metabolic dysregulation and subsequent inflammation. In this review, we summarize the contributions of macrophages to four metabolic conditions – diabetes and adipose tissue inflammation, atherosclerosis, non-alcoholic fatty liver disease and neurodegeneration. The role of macrophages is complex, yet they hold great promise as potential therapies to address these growing health concerns.